Pengaruh Self Efficacy, Presepsi Guru, dan Harapan Masa Depan terhadap Minat Menjadi Guru pada Mahasiswa Pendidikan Ekonomi Angakatan 2021 FEB UNNES - Putri Kharomah; Suratno Suratno (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of self-efficacy, perceptions of the teaching profession, and future expectations on the interest in becoming a teacher among 2021 Economics Education students at the Faculty of Economics and Business, Semarang State University (FEB UNNES). The background of this study is based on the phenomenon of declining interest among education students in pursuing a career as a teacher, despite their academic preparation for it. This study employs a quantitative approach using a survey method with 204 respondents selected proportionally from three education programs. Data collection was conducted using a Likert scale-based questionnaire and analyzed using multiple linear regression with the assistance of SPSS 23 software. The results of the study indicate that all three independent variables have a positive and significant influence on interest in becoming a teacher. Self-efficacy has an influence with a regression coefficient of 0.271 (p = 0.002), perception of the teaching profession with 0.228 (p = 0.019), and future expectations as the most dominant variable with a regression coefficient of 0.358 (p = 0.000). Simultaneously, the three variables significantly influence interest in becoming a teacher with a significance value of 0.000 and an Adjusted R² value of 0.182, indicating that the regression model explains 18.2% of the variance in students' interest in becoming teachers. These findings highlight the importance of strengthening self-efficacy, positive perceptions of the profession, and positive future expectations in enhancing students' interest in the teaching profession.